2019
DOI: 10.1002/mc.23139
|View full text |Cite
|
Sign up to set email alerts
|

mPRα mediates P4/Org OD02‐0 to improve the sensitivity of lung adenocarcinoma to EGFR‐TKIs via the EGFR‐SRC‐ERK1/2 pathway

Abstract: The discovery of epidermal growth factor receptor (EGFR) mutations has made EGFR tyrosine kinase inhibitors (EGFR‐TKIs) a milestone in the treatment for advanced non–small cell lung cancer (NSCLC). However, patients lacking EGFR mutations are not sensitive to EGFR‐TKI treatment and the emergence of secondary resistance poses new challenges for the targeted therapy of lung cancer. In this study, we identified that the expression of membrane progesterone receptor α (mPRα) was associated with EGFR mutations in lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…In addition, high FGL1 expression may be related to the expression level of EGFR, which has been reported in L02 cells and several studies on liver injury [19,30,45,46]. FGL1 can inhibit L02 cell proliferation induced by activating the non-receptor tyrosine kinase SRC to induce EGFR phosphorylation [21]. It has also been observed that apoptosis of NSCLC cells is induced by inhibition of EGFR/STAT3 activation and promotion of PARP1 cleavage, regardless of the mutation status of EGFR [47].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In addition, high FGL1 expression may be related to the expression level of EGFR, which has been reported in L02 cells and several studies on liver injury [19,30,45,46]. FGL1 can inhibit L02 cell proliferation induced by activating the non-receptor tyrosine kinase SRC to induce EGFR phosphorylation [21]. It has also been observed that apoptosis of NSCLC cells is induced by inhibition of EGFR/STAT3 activation and promotion of PARP1 cleavage, regardless of the mutation status of EGFR [47].…”
Section: Discussionmentioning
confidence: 74%
“…Further, substantial evidence indicates that numerous cytokines related to cell proliferation play key roles in pathways that promote tumor cell proliferation and suppress their apoptosis [ 14 , 15 ], thereby significantly affecting patient prognosis. Benefited from the results above, some corresponding inhibitors like MEK inhibitors (trimetazidine) [ 16 , 17 ], MET-TKIs (tepotinib and cabozantinib) [ 18 , 19 ], PI3K inhibitor [ 20 ], and STAT3 and Src inhibitors [ 21 , 22 ] have been developed widely applied in clinical and showing good clinical effects. Some newly discovered cytokines, including YES (pp62c-yes) [ 23 ], YES/YES-associated protein 1 [ 24 ], and NF-1 [ 25 ], can increase the sensitivity of NSCLC cells to EGFR-TKIs by activating the AKT or MAPK pathway, showing great research benefits.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of P4 receptor expression in lung cancer tissues varies and it remains controversial as to whether it can predict the prognosis of lung cancer patients. Lu et al 22 demonstrated that mPRα expression was positively correlated with female gender, welldifferentiated status and a better prognosis in lung cancer patients. In addition, we previously showed that P4 reverses the EMT and inhibits lung cancer cell migration and invasion by binding to the mPRα.…”
Section: Zuomentioning
confidence: 99%
“…In addition, we previously showed that P4 reverses the EMT and inhibits lung cancer cell migration and invasion by binding to the mPRα 23 . P4 treatment can also re‐sensitize lung cancer cells to gefitinib, an epidermal growth factor receptor tyrosine kinase inhibitor, and inhibit cell proliferation 22 . Nevertheless, the events mediating the protective effects of P4 in lung cancer are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Further, substantial evidence indicates that numerous cytokines related to cell proliferation play key roles in pathways that promote tumor cell proliferation and suppress their apoptosis [14,15], thereby signi cantly affecting patient prognosis. Bene ted from the results above, some corresponding inhibitors like MEK inhibitors (trimetazidine) [16,17], MET-TKIs (tepotinib and cabozantinib) [18,19], PI3K inhibitor [20], and STAT3 and Src inhibitors [21,22] have been developed widely applied in clinical and showing good clinical effects. Some newly discovered cytokines, including YES (pp62c-yes) [23], YES/YES-associated protein 1 [24], and NF-1 [25], can increase the sensitivity of NSCLC cells to EGFR-TKIs by activating the AKT or MAPK pathway, showing great research bene ts.…”
Section: Introductionmentioning
confidence: 95%